2000
DOI: 10.1111/j.1749-6632.2000.tb05493.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Definitive Severe Mitochondrial Signs and Symptoms among Deceased HIV‐Uninfected and HIV‐Indeterminate Children ≤ 5 Years of Age, Pediatric Spectrum of HIV Disease Project (PSD), USA

Abstract: Background: In response to recent reports of mitochondrial dysfunction in HIV‐uninfected infants exposed to antiretroviral (ARV) prophylaxis, the Perinatal Safety Review Working Group reviewed deaths in five large HIV‐exposed perinatal cohorts in the United States to determine if similar cases of severe mitochondrial toxicity could be detected. We describe the results of this review for the PSD cohort. Methods: Hospitalization, clinic and death records for deceased HIV‐uninfected and HIV‐indeterminate childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…Our analysis included only infants with exposure to three or more ARV drugs in utero since this is the treatment regimen most relevant to the current international treatment guidelines for HIV-positive pregnant women and because women not on ARVs during pregnancy likely differ in important ways from those who have access to care and are treated with ARVs. The findings of this investigation are consistent with those of previous studies that found no association between in utero ARV exposure and neurologic outcomes, such as MD, [10][11][12][13]20,21 neurologic events, 14,21 and congenital abnormalities 15 among HEU infants. However, there are other studies that did find associations between in utero ARV exposure and MD, 4,8 hyperlactatemia, 22 febrile seizures, 6 and neurologic dysfunction.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our analysis included only infants with exposure to three or more ARV drugs in utero since this is the treatment regimen most relevant to the current international treatment guidelines for HIV-positive pregnant women and because women not on ARVs during pregnancy likely differ in important ways from those who have access to care and are treated with ARVs. The findings of this investigation are consistent with those of previous studies that found no association between in utero ARV exposure and neurologic outcomes, such as MD, [10][11][12][13]20,21 neurologic events, 14,21 and congenital abnormalities 15 among HEU infants. However, there are other studies that did find associations between in utero ARV exposure and MD, 4,8 hyperlactatemia, 22 febrile seizures, 6 and neurologic dysfunction.…”
Section: Discussionsupporting
confidence: 82%
“…9 Beyond the IMPAACT P1025 results, findings from the initial FPCS were not supported by results from many other groups, including investigators from several US cohorts who reviewed >20,000 HEU subjects and found no deaths due to MD. [10][11][12][13] However, these US-based studies were limited to evaluating causes of mortality and were not able to assess neurologic morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…10 To date, reports concerning NRTI toxicity in children who are exposed perinatally to ARV are contradictory. Although large population-based studies have failed to demonstrate signs or symptoms suggesting mitochondrial injury in NRTI-exposed HIVuninfected children, 9,[11][12][13] other authors have reported rare severe neurologic damage consistent with mitochondrial dysfunction 14,15 and a higher risk of febrile seizures below the age of 18 months 16 in these otherwise healthy patients. The aim of our study was to determine the prevalence, clinical consequences, evolution, and risk factors for hyperlactatemia (HLA) in our cohort of HIV-uninfected infants who were exposed to ARV during gestation, labor, and/or the neonatal period.…”
mentioning
confidence: 99%
“…Mitochondrial dysfunction should be considered in children with perinatal ARV exposure who present with severe clinical findings of unknown etiology, particularly neurologic findings. [67][68][69][70][71][72][73][74] Information regarding in utero and/or neonatal ARV exposure should be part of the ongoing permanent medical chart of the child, particularly for uninfected children. Children with in utero ARV exposure who develop significant organ-system abnormalities of unknown etiology, particularly of the nervous system or heart, should be evaluated for potential mitochondrial dysfunction.…”
Section: Long-term Toxicitymentioning
confidence: 99%
“…[64][65][66][67] However, should an infant develop severe clinical symptoms of unknown etiology, particularly neurologic symptoms, serum lactate concentration should be determined. If the serum lactate con-centration is significantly abnormal in an infant with compatible clinical symptoms, an expert in pediatric HIV-1 infection should be consulted regarding potential early discontinuation of prophylaxis.…”
Section: Monitoring For and Management Of Short-term Toxicity During mentioning
confidence: 99%